2022
DOI: 10.2478/hjbpa-2022-0006
|View full text |Cite
|
Sign up to set email alerts
|

Smart City Readiness in South African Municipalities: A Qualitative Study

Abstract: This study investigated the meaning of a smart city concept, the limitations of municipal role players to adopt the smart city, and the recommendations to facilitate the adoption of a smart city concept in the municipalities of the North West province. A qualitative research approach was adopted to collect data from the participants, which facilitated adequate interactions with the participants through open-ended interviews. Twenty participants were selected purposively to participate in this study through an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Other major factors that impact the readiness of the state to accept smart cities identified in the scholarly literature and valid for the context of Australian smart cities entail: In a study of the readiness of Russian municipalities it is discovered that the digital rate, clear objectives, and targets of the digitalization process, as well as financial and organizational resources, contribute to enhancing the smart city readiness of local and national institutions [61]. Furthermore, another research presents the limited financial resources, lack of adequate infrastructure, strategic leadership and investors, inefficient decision-making process, inability to implement the outcomes from research, as well as corruption among the role players are significant factors deterring the readiness of municipalities in South Africa to accept and implement smart city projects [62]. In addition to that, the population shift from rural to urban areas in the case of emerging economies, requires the state to develop sufficient expertise in educating the potential users of smart city services as a critical step toward enhancing the city's readiness to withstand any possible emerging problems [63].…”
Section: State Readinessmentioning
confidence: 99%
“…Other major factors that impact the readiness of the state to accept smart cities identified in the scholarly literature and valid for the context of Australian smart cities entail: In a study of the readiness of Russian municipalities it is discovered that the digital rate, clear objectives, and targets of the digitalization process, as well as financial and organizational resources, contribute to enhancing the smart city readiness of local and national institutions [61]. Furthermore, another research presents the limited financial resources, lack of adequate infrastructure, strategic leadership and investors, inefficient decision-making process, inability to implement the outcomes from research, as well as corruption among the role players are significant factors deterring the readiness of municipalities in South Africa to accept and implement smart city projects [62]. In addition to that, the population shift from rural to urban areas in the case of emerging economies, requires the state to develop sufficient expertise in educating the potential users of smart city services as a critical step toward enhancing the city's readiness to withstand any possible emerging problems [63].…”
Section: State Readinessmentioning
confidence: 99%
“…Sixty per cent or more of the government agencies surveyed in the Regency of North Penajam Paser reported that they were prepared to develop a smart city. The readiness of a smart city necessitates the application of innovation in technology, information, and communication, particularly in the dissemination of information to citizens to improve their performance, service quality, and welfare (Enwereji & Uwizeyimana, 2022). In addition, the report places little emphasis on the city's preparedness to adopt the concept, focusing instead on concerns regarding the availability of infrastructure and the skills of the community.…”
Section: Local Government and Community Readiness In Supporting The D...mentioning
confidence: 99%